Tell a Story to Save a River: Assessing the Impact of Using a Children’s Book in the Classroom as a Tool to Promote Environmental Awareness - Aurélio, Luísa; França, Susana; Sequeira, Vera; Boaventura, Diana; Correia, Maria João; Pinto, Bruno; Amoroso, Sandra; Feio, Maria João; Brito, Cristina; Chainho, Paula; Chaves, Luísa (Frontiers in Marine Science, 2021)
Listening to a story stimulates children to understand concepts and vocabulary, while developing their background knowledge. Previous research indicates that the use of scientifically accurate literature helps children connect to the natural world. Promoting environmental education (EE) should be of utmost importance in school curricula, providing opportunities to students to improve their knowledge regarding the environment, and how to protect it. Particularly, marine ecosystems have been subject to increasing pressures, highlighting the importance of taking Ocean Literacy (OL) to the classroom. Drawing attention to more relatable environments, like a river, by tailoring OL activities to local contexts and community interests, might be an efficient strategy to raise awareness of ocean problems. A children’s book, written by a MARE (Marine and Environmental Sciences Centre, Portugal) researcher, with a macrobenthic invertebrate as the main character, was the springboard for an outreach project, developed with elementary school students. The project aimed to assess the impact of using a children’s book as a tool to promote environmental awareness, focusing on river basin ecological issues. Researchers conducted reading sessions of the book with 89 female and 87 male elementary school students (ages between 8–10). The target audience were students from two public and two private schools from an urban city and a city with a strong fishing tradition, aiming to assess if the reading session impacted students differently according to their background. A sequential explanatory mixed methodology was applied, using a pretest-posttest design, combined with focus group interviews in the last phase, to measure change in students’ knowledge, before and after the reading. Results demonstrated that there was an overall improvement in students’ knowledge regarding river basin biodiversity and anthropogenic threats they are subjected to. Furthermore, the idea that local impacts on rivers will also reach and influence the ocean was always present throughout the reading sessions. Students’ background, such as the type of school and region influenced higher posttest score results. In particular, students from Lisbon had higher scores in posttest results, while the same was observed for students from private schools. The present research revealed that a children’s book is an effective tool to improve environmental knowledge, while being an entertaining activity for students.